1991
DOI: 10.1159/000276242
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Electronystagmographic Abnormalities in Patients with Type I Diabetes mellitus

Abstract: Only a few studies have investigated vestibular function in diabetes mellitus (DM), showing contradictory results. We have performed an electronystagmographic (ENG) evaluation of 46 individuals with type I DM and 37 healthy controls. No patient reported subjective vestibular symptoms. Duration of caloric-induced nystagmus (DN) was significantly lower (2.1 ± 0.7 vs. 2.6 ± 0.4 min, p < 0.01), and central nystagmus frequency of caloric response also nonsignificantly tended to be decreased (37.4 ± 16.5 vs. 41.7 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
32
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 6 publications
11
32
0
1
Order By: Relevance
“…Some reports show an improper electronystagmographic results in 50% of diabetic patients without any subjective symptoms [4]. Nevertheless the authors showed a correlation between electronystagmographic disturbances and duration of diabetes, positive correlation between electronystagmographic disturbances and diabetic complications and no correlation between electronystagmographic results and glycated haemoglobin concentration [4]. Similar to our results the disturbances were mostly of central type.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Some reports show an improper electronystagmographic results in 50% of diabetic patients without any subjective symptoms [4]. Nevertheless the authors showed a correlation between electronystagmographic disturbances and duration of diabetes, positive correlation between electronystagmographic disturbances and diabetic complications and no correlation between electronystagmographic results and glycated haemoglobin concentration [4]. Similar to our results the disturbances were mostly of central type.…”
Section: Discussionsupporting
confidence: 86%
“…Some authors state that longer or shorter periods of hypoglycaemia have an important influence on diabetic encephalopathy occurrence [20]. Those results are inconsistent with data of other authors who did not show any correlation of electronystagmographic disturbances and hypoglycaemic incidents [4,18,19].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In a sample of 46 Type I Diabetes mellitus patients, Biurrun 12 did not find any vestibular symptoms complaint, and 12 individuals showed vectoelectronystagmography alteration (2 individuals with labyrinthine predominance and 10 other individuals with directional preponderance). Rybak4 mentions a high rate of abnormalities seen at the vectoelectronystagmographic results in Diabetes mellitus patients who complained of dizziness.…”
Section: Discussionmentioning
confidence: 88%